A formação em Psicologia para o compromisso social: um estudo de cursos em São Paulo - Rechtman, Raizel (2019)
The beginning of the history of Psychology in Brazil was marked by a commitment to the elites and to exclusionary and pathologizing practices. It was only after the constitution of a professional project of social commitment that this reality began to change. From its objective to contribute to the advance of this new project in Psychology, this research sought to understand how we form socially committed psychologists. To this end, group interviews were conducted with students attending the last year of the Psychology course of two higher education institutions located in the city of São Paulo (SP). For these interviews, a script was elaborated from the fields of expression of social commitment developed by Santos (2017). We identified different resources that help the training for the social commitment professional project in Psychology, particularly the internships, the relationship with teachers and course directors, and extracurricular activities. Beyond the description of formative resources, we developed four guiding dimensions for a Psychology training focused on social commitment (Guarantee of Praxis, Critical notion of the constitution of the subject, Care of pedagogical practices and Understanding of Psychology as a Science-Profession), with the goal of producing references and disseminating possibilities of formative practices towards a profession committed to the Brazilian reality